2011
DOI: 10.1088/1367-2630/13/6/065014
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the cuprate superconducting and pseudogap phases from spectroscopic imaging STM

Abstract: Abstract. We survey the use of spectroscopic imaging scanning tunneling microscopy (SI-STM) to probe the electronic structure of underdoped cuprates. Two distinct classes of electronic states are observed in both the d-wave superconducting (dSC) and the pseudogap (PG) phases. The first class consists of the dispersive Bogoliubov quasiparticle excitations of a homogeneous d-wave superconductor, existing below a lower energy scale E = 0 . We find that the Bogoliubov quasiparticle interference (QPI) signatures of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 114 publications
5
60
0
5
Order By: Relevance
“…We find that V CDW is neither equivalent to the Fermi velocity seen in ARPES nor the quasi-particle-interference dispersion seen in STM 21 (Supplementary Information), indicating that the weak-coupling fermiology may be irrelevant for describing the observed dispersion. Temperature-dependent measurements were conducted on another Bi2212 crystal with a similar T c (40 K), with results shown in Fig.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…We find that V CDW is neither equivalent to the Fermi velocity seen in ARPES nor the quasi-particle-interference dispersion seen in STM 21 (Supplementary Information), indicating that the weak-coupling fermiology may be irrelevant for describing the observed dispersion. Temperature-dependent measurements were conducted on another Bi2212 crystal with a similar T c (40 K), with results shown in Fig.…”
mentioning
confidence: 73%
“…We choose the double-layer cuprate Bi 2.2 Sr 1.8 Ca 0.8 Dy 0.2 Cu 2 O 8+δ (Bi2212), whose electronic structure has been extensively studied by surface-sensitive spectroscopy, such as scanning tunnelling microscopy 21 and angle-resolved photoemission 22 , and in which a short-range CDW order was recently reported 7,8 . With improved energy resolution up to 40 meV, we see additional features in the previous quasi-elastic region (Fig.…”
mentioning
confidence: 99%
“…The low energy 'V-shaped' region of the LDOS(E) are the energies where the coherent excitations of the Bogoliubov quasiparticles from the superconducting condensate reside 10 . These excitations present themselves as the dispersive QPI, seven vectors in q-space that emanate from the eight ends of the superconducting band structure 1,4,15 .…”
Section: Cuprate Electronic States and Phenomena Backgroundmentioning
confidence: 99%
“…Due to the short length scale of this disorder, the only method capable of directly probing it is spectroscopic imaging scanning tunneling microscopy (SI-STM). This technique produces data sets that contain detailed information about both the spatial and energy dependence of the quasiparticle interference (QPI) of Bogoliubov quasiparticles [1][2][3][4][5] , the checkerboard 3,6 and the pseudogap states [7][8][9][10] . It has been recently shown that the low energy empty states electronic structure (positive energies) can be classified into three energy scales using the Tripartite model 11 , which is a phenomenological model explaining from both q-space and r-space SI-STM data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation